Qatari Support for Syrian Refugee Camps (2011–2018): Dukungan Qatar bagi Kamp Pengungsi Suriah (2011–2018) - Al-Sinjari, Mohammed Nouri Khalaf; Hussein, Assist. Prof. Dr. Mohammed Hamza (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Regional crises in the Middle East have reshaped diplomatic interactions and foreign policy strategies among key actors. Specific Background This study examines Qatari foreign policy within the context of the Syrian and Yemeni crises, focusing on its diplomatic roles and regional engagement. Knowledge Gap Existing studies have not sufficiently clarified how Qatar balances mediation and direct involvement within complex regional conflicts. Aims This research aims to analyze the evolution of Qatari foreign policy and its positioning in regional crises. Results The findings show that Qatar adopts flexible diplomatic strategies, combining mediation efforts with active political engagement to respond to shifting regional dynamics. Novelty The study provides an integrated analysis of Qatar’s foreign policy behavior across multiple crises, highlighting its adaptive and multi-dimensional approach. Implications The results suggest that small-state diplomacy can play a significant role in regional conflict management through strategic flexibility and diversified engagement. Keywords: Qatari Foreign Policy, Regional Crises, Middle East Politics, Diplomacy, Strategic Behavior Key Findings Highlights Diplomatic roles shift between mediation and active engagement Regional interactions reflect adaptive policy responses Crisis dynamics shape strategic decision making